Potensi Alisin bagi Kedokteran Gigi - Fonda, Gloria; Natassya, Priska; Nugrogo, Didi (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Allicin is an organosulfur compound commonly found in garlic that has been used as a traditional medicine. It can act as an antibacterial, antivirus, antifungal, anti-inflammatory, anticancer, antioxidant, and immunomodulator. Studies showed that allicin has potential to be used as a medicine to prevent caries and periodontal bacteria, prevent denture stomatitis, and alleviate oral cancer pain. It is also easy to obtain, affordable, and not toxic. Therefore, allicin has the potential to be used in the field of dentistry.